2019
DOI: 10.1111/maec.12556
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the rocky intertidal periwinkle Echinolittorina paytensis through a biogeographic transition zone in the Southeastern Pacific

Abstract: Barriers to dispersal are recognized to play an important role in the differentiation of populations and ultimately in speciation. In the southeast Pacific, on the northern coast of Peru, a transition zone between the Peruvian and Panamic marine biogeographic provinces exists. Here, the convergence between two contrasting surface currents could generate a barrier effect for the larval dispersal of meroplanktonic invertebrates, which could in turn generate differentiated populations or genetic lineages on both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…The formation and removal of barriers have occurred repeatedly over geologic time [5] and such broad scale processes modify inter-oceanic migration of shallow coastal marine faunas. Barrier formation fosters speciation as the original range of a species is divided up and divergent changes in the isolated populations are expected [6][7][8][9]. Genetic analyses shed light on the origin of populations and individuals and their range expansion through geological times.…”
Section: Introductionmentioning
confidence: 99%
“…The formation and removal of barriers have occurred repeatedly over geologic time [5] and such broad scale processes modify inter-oceanic migration of shallow coastal marine faunas. Barrier formation fosters speciation as the original range of a species is divided up and divergent changes in the isolated populations are expected [6][7][8][9]. Genetic analyses shed light on the origin of populations and individuals and their range expansion through geological times.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, on the southeast coast of Australia, a biogeographical barrier called the Southeast Australian Biogeographic Barrier (SEABB) occurs, which plays an important role in shaping species distribution and phylogeographic patterns (Ayre et al, 2009;Ayre & Rosser, 2021;Waters, 2008). Similar biogeographical barriers occur in the southeast Pacific on the northern coast of Peru (Barahona et al, 2019), the west coast of the United States (Burton, 1998;Palumbi, 1996;Taylor & Hellberg, 2006), the east coast of North America (Pappalardo et al, 2015), the Atlantic-Mediterranean coast (El Ayari et al, 2019), and the coast of China (Dong et al, 2012;Liu, 2013). These barriers are not hard and fast, however, but shift when environmental changes occur.…”
Section: Coastal Biogeographical Pattern and Biogeographical Barriersmentioning
confidence: 99%
“…A growing amount of evidence has suggested that post-settlement establishment plays a more important role in the maintenance of biogeographic breaks in the oceans than larval dispersal (Keith et al, 2015). Invertebrates usually exhibit high rates of post-settlement mortality, which are mainly due to the delay of metamorphosis, competition, predation, physiological stress (Hunt & Scheibling, 1997) and genetic inviability driven by genotype-environment interactions (Barahona et al, 2019;Plough et al, 2016). Importantly, the capacity of species to tolerate physiologically marginal conditions influences their ability to establish a viable population after successful dispersal (Keith et al, 2015) and the persistence of their present distribution ranges (Dong et al, 2015;Han et al, 2019).…”
Section: Post-settlement Establishment and Global Warmingmentioning
confidence: 99%
“…The Peruvian scallop has a moderate pelagic larval duration of 16-25 days in the water column, depending on the water temperature, before settlement (von Brand, Merino, Abarca, & Stotz, 2006). The combination of the northward passive larval displacement caused by the Peruvian Coastal Current (PCC) and the southward displacement caused by the movement of warm water masses during ENSO events could facilitate the bidirectional population connectivity (Barahona et al, 2019). The recolonization of extinct natural beds (Wolff & Mendo, 2000) and the formation of temporal intermediate aggregations (Ysla, 2009) during and after ENSO could increase the genetic connectivity.…”
Section: Population Structure and Gene Flow Analysismentioning
confidence: 99%